Digitally fabricated multi-modal wireless sensing using a combination of printed sensors and transistors with silicon components. (23rd August 2017) - Whiting, G L; Schwartz, D E; Ng, T N; Krusor, B S; Krivacic, R; Pierre, A; Arias, A C; Härting, M; van Buren, D; Short, K L
Abstract: Printing is a promising manufacturing approach for the fabrication of flexible, large-area, custom sensor systems for applications such as wearable electronics and sensor labels. While printed examples of many physical and chemical sensors have been demonstrated, functionality useful for stand-alone systems such as high-resolution analog-to-digital conversion and wireless communication to address these sensors is not currently available in circuits printed entirely from solution. In order to retain the benefits of print manufacturing without sacrificing performance, a hybrid approach can be followed where printed and pre-fabricated devices are used together. In this report a mostly-printed wireless light and temperature sensor system that operates at 3.6 V and reports light and temperature readings wirelessly with a sensitivity of 0.7 °C and 2.5 μ W cm −2 at 500 nm respectively is demonstrated. The number of printed components was maximized and off-the-shelf microfabricated devices were only introduced where functionality is not currently achievable through printing. Onto a flexible polyester substrate, print processes were used to fabricate the bulk-heterojunction photodiode, thermistor, low-voltage operation multiplexing transistors, antenna, passives and interconnects, and silicon ICs are used for signal processing, memory and wireless communication. The printed components (sensors and transistors) were specifically developed to facilitate electrical integration into the hybrid system.